Econometric Evidence on Self-Determination Theory in Learning Calculus Among Agribusiness Students - Leomarich F Casinillo; Emily L Casinillo (Universitas Negeri Surabaya, 2020)
Self-determination theory is a study of individual interest and motivation which plays a vital role in good and productive performance in learning. This study focus on the agribusiness students motivation in learning Calculus as part of their curriculum. Using econometric models, this study identified some statistically significant factors of motivation. The study employed 121 agribusiness students as respondents using stratified random sampling in the first semester of SY 2019-2020. Results revealed that most of the agribusiness students are motivated in learning calculus. Female student is more likely motivated compared to male students. Females are more focusing on their studies while males are affected by online games. The study revealed that learning attitude and health are significant factors of motivation in learning. Also, students experience in calculus makes them creative in the classroom which positively contributes to their interest. Perhaps, this students makes or invents new ideas in the learning environment. Results documented that problems encountered in the classroom does not affects their interest in learning. Furthermore, results showed that their perception to their calculus teacher is relatively high which is a significant factor to their motivation. In fact, their teachers are the most important factor that contributes to their level of achievement in Calculus, more important than any other school resources.